2007
DOI: 10.1097/brs.0b013e318074d515
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Trunk-Flexed Postures on Balance and Metabolic Energy Expenditure During Standing

Abstract: Compensatory actions, such as ankle plantarflexion and hip flexion, allowed the mean position of the net COP to remain within a narrowly defined region irrespective of trunk posture. Changes in muscle activity associated with a trunk-flexed posture and the associated compensations likely contributed to the increased energy expenditure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 15 publications
0
30
0
1
Order By: Relevance
“…Potentially, differences in posture and consequently muscular effort to support the body against gravity could play a role. However, Saha et al [21], who studied the effect of trunk orientation on the energy consumption of upright standing, found that an increase in energy consumption of 60%, as found in our study, would require a forward lean of the trunk of 508. Although posture was not quantified in our study, no such obvious postural changes were observed in any of the imposed conditions.…”
Section: Discussionmentioning
confidence: 44%
“…Potentially, differences in posture and consequently muscular effort to support the body against gravity could play a role. However, Saha et al [21], who studied the effect of trunk orientation on the energy consumption of upright standing, found that an increase in energy consumption of 60%, as found in our study, would require a forward lean of the trunk of 508. Although posture was not quantified in our study, no such obvious postural changes were observed in any of the imposed conditions.…”
Section: Discussionmentioning
confidence: 44%
“…In one study, healthy subjects were asked to maintain upright, 25° and 50° flexed postures during standing while their energy consumption was monitored. 164 To maintain balance and keep their center of pressure in the same fore-aft position under their base of support, the subjects employed a number of compensatory strategies including increased hip flexion and ankle plantarflexion and increased cervical spine lordosis, which resulted in increased oxygen consumption (25° and 50° flexion increased consumption by 28% and 60%, respectively, over upright standing). Standing subjects who were directed to change their pelvic tilt angle showed an unconscious equivalent but opposite change in spinal curvature to compensate for the change in balance.…”
Section: Perturbing the Balanced Spinementioning
confidence: 99%
“…This option would be expected to encourage more time spent standing and in light ambulatory movement, improved postural control and function, and increased muscular activity and energy expenditure. 18,19 The integration of classroom desks which reduce the time that students spend sitting is a promising target for children's health promotion initiatives. Indeed, an increasing number of interventions have been tested by using this approach, but the relevant evidence has yet to be synthesized.…”
mentioning
confidence: 99%